Nuclear Heme oxygenase-1 is associated to tumor progression in Human Head and Neck Carcinoma. - Gandini, Norberto Ariel (2012)
The expression of heme oxygenase-1 (HO-1) was shown to be increased in multiple tumors compared with their surrounding healthy tissues and was also observed to be up-regulated in oral squamous cell carcinomas (OSCC). However, conflicting results were obtained and little information is available regarding HO-1 significance in head and neck squamous cell carcinoma (HNSCC). Therefore, the aim of the present study was to perform a wide screening of HO-1 expression in a large collection of human primary HNSCCs and to correlate the results with clinical and pathological parameters. For this purpose, we investigated the expression of this protein by immunohistochemistry (IHC) in tissue microarrays (TMAs) of HNSCC and in an independent cohort of paraffin-embedded tumor specimens. HO-1 expression was further validated by real-time qPCR performed on selected laser capture-microdissected (LCM) oral tissue samples. Both the number of HO-1-positive samples and HO-1 immunoreactivity in the cancerous tissues were significantly higher than those in the non-tumor tissues. These results were confirmed at the mRNA level. Interestingly, HO-1 localization was observed in the nucleus, and the rate of nuclear HO-1 in HNSCC was higher than that in non-malignant tissues. Nuclear HO-1 was observed in HNSCC cell lines and increased even further following hemin treatment. Analysis of HO-1 expression and sub-cellular localization in a mouse model of squamous cell carcinoma (SCC) and in human HNSCC revealed that nuclear HO-1 increases with tumor progression. Taken together, these results demonstrate that HO-1 is up-regulated in HNSCC and that nuclear localization of HO-1 is associated with malignant progression in this tumor type.